What Factors Drive Outward FDI by Chinese Multinationals? A Study of Three Cases - LU, YUN (2010)
this study fills the previous researching gap, using integrating theoretical insights from three fundamental theories: resource-, industry, and institution-based view to examine the determinants of Chinese MNEs’ internationalization. Using three case firms, the analysis indicates that both industrial competitions and the government support of firms’ home country play an important role in driving firms’ internationalization, whilst the traditional view that firms’ ownership advantage will drive firms to invest abroad cannot explain Chinese firms’ OFDI activities.